The Effectiveness of Using PowerPoint (PPT) To Improve Understanding of Arabic Grammar Googel Slides at Al - Azhar Jember High School - Abdillah, Muhammmad Shefi Ainur Rohman (Yayasan Al-Aziziyah Tlogoagung Kedungadem Bojonegoro, 2024)
Learning Arabic grammar is often considered difficult by students because of its abstract and textual presentation, without the support of visualization or interactive media. Often teachers only rely on textbooks or blackboards, making the learning process monotonous and less interesting. This research aims to determine the use and effectiveness of power points in improving understanding of Arabic grammar at Al-Azhar Islamic Middle School Jember. Data collection methods include observation, unstructured interviews, tests (pre- and post-test), and documentation. Data analysis was carried out using normality, homogeneity and t tests using SPSS for Windows 25. The research results showed that the teaching process using included steps such as introducing methods, presenting material, providing examples, discussions and practical exercises. The effectiveness of using Power Point was proven by the results of the normality test which showed normal data distribution in the experimental group (p=0.059) and control (p=0.092). The t test shows that the t value (4.507) is greater than the t table (1.68023), which means that the use of power point is effective in improving understanding of Arabic grammar at Al-Azhar Islamic Middle School Jember in the 2023/2024 academic year.